PRESERVATION OF INTANGIBLE CULTURAL HERITAGE THROUGH THE LAKE TOBA TRADITIONAL MUSIC FESTIVAL - Bangun, Jabatin; Sudirga, I Komang; Remawa, Anak Agung Gede Rai; Muka, I Ketut (International Journal of Multidisciplinary Research and Literature, 2026)
Intangible Cultural Heritage requires various new strategies and methods to address preservation challenges in the modern era. One effective approach is through festivals as a medium for introduction, collaboration, and regeneration of cultural works. This paper examines the 2021 Lake Toba Traditional Music Festival as a model of preservation based on creative participation. This festival involved twelve composers selected through an open selection process by a team of curators to create a musical work sourced from the traditions of four ethnic groups around Lake Toba: Batak Toba, Karo, Simalungun, and Pakpak. Each composer was required to conduct field research and interact directly with local musicians to understand the musical, social, and ecological contexts of the cultures they were adapting. This research uses participatory qualitative methods with data sources in the form of field observations, interviews, audiovisual documentation, and festival archives. The analysis is carried out using a musicological and ethnographic approach to examine the cross-cultural creative process. The results of the research show that this program produces a diversity of musical forms that combine instrumental, vocal, and traditional poetry elements, as well as revealing a dialogue between modernity and tradition. This festival is not only a performance event, but also a space for transcultural creation that strengthens the cultural identity and musical ecology of the Lake Toba region.